2011
DOI: 10.1038/cddis.2010.90
|View full text |Cite
|
Sign up to set email alerts
|

WRAP53 promotes cancer cell survival and is a potential target for cancer therapy

Abstract: We previously identified WRAP53 as an antisense transcript that regulates the p53 tumor suppressor. The WRAP53 gene also encodes a protein essential for Cajal body formation and involved in cellular trafficking of the survival of motor neuron complex, the telomerase enzyme and small Cajal body-specific RNAs to Cajal bodies. Here, we show that the WRAP53 protein is overexpressed in a variety of cancer cell lines of different origin and that WRAP53 overexpression promotes cellular transformation. Knockdown of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 29 publications
5
68
0
Order By: Relevance
“…So here we used TCAB1 to represent the WRAP53 isoforms except α. Previously reported data in vitro suggested that overexpression of WRAP53 could induce cellular transformation while WRAP53 knockdown by exogenous siRNA on the other hand, could induce cellular apoptosis [16], also indicating potential oncogenic characteristics of TCAB1. Head and neck carcinoma is approximately the sixth most common cancer among global cancers [17,18], and the five year survival rate has remained at about 50% in the past decades [19].…”
Section: Introductionmentioning
confidence: 99%
“…So here we used TCAB1 to represent the WRAP53 isoforms except α. Previously reported data in vitro suggested that overexpression of WRAP53 could induce cellular transformation while WRAP53 knockdown by exogenous siRNA on the other hand, could induce cellular apoptosis [16], also indicating potential oncogenic characteristics of TCAB1. Head and neck carcinoma is approximately the sixth most common cancer among global cancers [17,18], and the five year survival rate has remained at about 50% in the past decades [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, inherited mutations in WRAP53b that affect its WD40 domain cause dyskeratosis congenita, a disorder involving bone marrow failure, premature aging, and cancer predisposition (Zhong et al 2011). Moreover, SNPs in WRAP53 or altered expression of the protein itself are associated with elevated risk for a variety of sporadic tumors and radioresistant head and neck cancer cells, hematoxicity, and disturbed DNA repair in workers exposed to benzene (Garcia-Closas et al 2007;Lan et al 2009;Schildkraut et al 2009;Mahmoudi et al 2011;Medrek et al 2013;Garvin et al 2014). Furthermore, patients with spinal muscular atrophy, a neurodegenerative disorder that is the leading genetic cause of infant mortality worldwide, exhibit loss of WRAP53b function (Mahmoudi et al 2010).…”
mentioning
confidence: 99%
“…Previous studies have provided evidence indicating that WRAP53 is a potential oncoprotein whose overexpression can induce cell transformation and promote cancer cell survival, and whose knockdown leads to massive cancer cell death (Mahmoudi et al, 2011). Mędrek et al (2013) found WRAP53 to be associated with ovarian cancer risk in a Polish population, although only in relation to its rs2287497 and rs2287498 polymorphisms.…”
Section: Discussionmentioning
confidence: 99%